(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Abortion has always been a topic of debate in the US social and legal context. This is an emblematic theme of how difficult it is to find a compromise on an ethical issue in a highly polarized society. The jurisprudential and normative approach through which the theme of the right to abortion has developed provides the researcher with many opportunities to evaluate the legal system. This article aims to trace the fundamental stages, in the American experience, of the complex and criticized jurisprudential affirmation of the right to abortion. Its purpose is to illustrate the articulated implications faced by abortion in American society. The article also examines the recent (highly controversial) Dobbs v. Jackson Women’s Health Organization decision by which the Supreme Court overruled Roe v. Wade jurisprudence.